Physiological aspectos on umbu tree - Filho, José Moacir Pinheiro Lima; Silva, Célia Maria M. de S. (Pesquisa Agropecuaria Brasileira, 2014)
The stomatal resistance, transpiration and leaf temperature of umbu tree (Spondias tuberosa Arr. Cam.) were evaluated in its natural environment, at the dry season and after the first rains. Stomatal resistance started to increase around 7:00 a.m. on both periods but more abruptly under drought conditions leading to a low transpiration. After raining, stomatal resistance started to increase before 1:00 p.m. when the environmental conditions were still favorable to a great evapotranspiratory demand, suggesting a very accentuated restriction of water loss by the umbu tree. No differences on leaf temperature related to both periods was recorded.